Radiographic Identification of Osseous Cyst- Like Lesions in the Distal Phalanx in 22 Lame Thoroughbred Horses Managed Conservatively and Their Racing Performance - Peter, Vanessa G.; O'Keeffe, Thomas A.; Smith, Lewis C. R.; Schweizer-Gorgas, Daniela (Frontiers in Veterinary Science, 2018)
To investigate the racing performance of Thoroughbred horses with osseous cyst-like lesions (OCLLs) in the distal phalanx causing lameness and treated conservatively. Objectives: To assess horses` ability to race and perform after radiographic identification of OCLL in the distal phalanx of Thoroughbred horses with lameness at the time of detection and undergoing conservative treatment. Study Design: Retrospective case control study. Methods: The clinical database of one equine clinic was reviewed in a ten-year period for Thoroughbreds showing lameness localised to the foot and a radiographic diagnosis of OCLL in the distal phalanx. Sex, age at time of detection of the OCLL, degree of lameness, affected limb and treatment were recorded. Successful performance of horses was assessed by racing at least once after detection of the OCLL and maximum racing performance rating (RPR). Radiographic features such as size, location, sclerotic rim and irregularity of the articular surface were compared to successful performance using univariable statistical analysis. Successful performance of horses with OCLL was compared to a control group of maternal siblings by parametric testing. Results: Twenty-two horses met the inclusion criteria. Thirteen horses raced after the detection of OCLLs. Eight did not race, one case had not yet reached racing age, resulting in 62% (13/21) of racing age racing at least once. The number of successfully performing horses with an OCCL was significantly lower compared to their maternal siblings (p=0.03, Odds ratio(OR) = 0.30). If horses with OCLL in the distal phalanx raced, their RPR was similar to their maternal siblings. No significant association was found between radiographic features of OCLLs and successful performance, but OCLLs in the left forelimb carried a more favourable outcome for racing (p=0.02, OR=2.33 95%CI 1.27, 4.27) compared to OCLLs in any other limb. Conclusions: Horses with lameness and an OCLL in the distal phalanx managed conservatively are less likely to race when compared to their maternal siblings. If horses with OCLLs in the distal phalanx are able to race, their performance, measured as RPR, was comparable to their maternal siblings. Due to the small numbers in this study the results should be interpreted carefully.